Particulate and dissolved forms of N,P, and organic C transported from major land uses in the Pagsanjan-Lumban catchment to Laguna de Bay, Philippines - Sanchez, Pearl B.; Oliver, Danielle P.; Kookana, Rai S. (2014)
The distribution of the particulate and dissolved forms of N, P and Organic C transported from major land uses in an agricultural watershed was determined. Total kjeldahl N (TKN), total P (TP) and total organic C (TOC) were determined in both unfiltered (total) and filtered (1.2 um) samples. The particulate fraction (1.2 um, a conservative estimate) tended to dominate offsite transport of TKN, TP and TOC from agricultural land uses, especially in regions with more intense cropping systems, namely Pagsanjan and Lucban [Philippines]. The average proportions of particulate forms of N and P (PN and PP) were higher at Pagsanjan which is a rice growing area (73% of TKN and 68% of TP than at Lucban (59% of TKN and 64% of TP), which is generally under vegetable production. At Cavinti (a site under coconut production), particulate forms of TKN and TP were dominant while the soluble fraction dominated TOC transport. For the piggery site at Majayjay, particulate forms controlled the movement of TKN and TOC while the soluble form dominated TP transport. A significant, positive relationship was observed between total suspended solids (TSS) and PN and between TSS and POC at all sites. A significant relationship between TSS and TP was only noted at Lucban. Overall, the study showed that despite the conservative estimate (1.2 um colloids only), particulate forms for C, N and P were the dominant fraction from all land uses in those agricultural catchments, except P from the piggeries site. The study suggests that the strategies to minimize or trap the particulate form may help reduce off-site migration of nutrients in the major catchment draining into Laguna de Bay, Philippines.
Keywords: Land use; Catchment basin; Watersheds; Laguna de Bay (Philippines)